2013
DOI: 10.1073/pnas.1311126110
|View full text |Cite
|
Sign up to set email alerts
|

Activation and control of p53 tetramerization in individual living cells

Abstract: Homo-oligomerization is found in many biological systems and has been extensively studied in vitro. However, our ability to quantify and understand oligomerization processes in cells is still limited. We used fluorescence correlation spectroscopy and mathematical modeling to measure the dynamics of the tetramers formed by the tumor suppressor protein p53 in single living cells. Previous in vitro studies suggested that in basal conditions all p53 molecules are bound in dimers. We found that in resting cells p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
108
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 27 publications
12
108
1
2
Order By: Relevance
“…Brightness values (Fig. 1B) are consistent with the dimer-to-tetramer transition recently reported in vivo (19), demonstrating the capability of the technique to discriminate between these oligomerization states. However, concerns regarding a possible artifact of the technique at the array need to be addressed.…”
Section: Significancesupporting
confidence: 87%
“…Brightness values (Fig. 1B) are consistent with the dimer-to-tetramer transition recently reported in vivo (19), demonstrating the capability of the technique to discriminate between these oligomerization states. However, concerns regarding a possible artifact of the technique at the array need to be addressed.…”
Section: Significancesupporting
confidence: 87%
“…These findings suggested to us that a dynamic intracellular population of metastable αS multimers and monomers coexists normally, and others have proposed similar models of dynamic/metastable tetramers (12), multimers (15), or "conformers" that may represent multimers (16). Analogous dynamic equilibria have been proposed for well-known tetrameric proteins such as hemoglobin (17) and p53 (18). An older study, from when αS was assumed to be solely monomeric, showed crosslinked low-n αS multimers in intact cells, and the authors discussed the possibility that synuclein normally exists in cells as low molecular mass oligomers, primarily dimers and trimers, that are in equilibrium with monomeric synuclein and are stabilized by experimentally induced covalent association (19).…”
supporting
confidence: 57%
“…2) on DNA, such as histone 2AX, and on checkpoint 2 protein kinase (Chk2), which, in turn, rapidly phosphorylates and activates p53 (42,43). Although phosphorylation of human p53 at Ser 20 by Chk2 is important for its transactivation of p21 CDKN1A (which encodes the cyclin-dependent kinase inhibitor 1A) and other stress response targets (44), p53 tetramerization is also essential for its activation (45,46).…”
Section: Stresses Trigger Autophagy Mtorc1 Has a Central Role In The mentioning
confidence: 99%